Does gold act as a hedge against inflation in the UK? Evidence from a fractional cointegration approach over 1257 to 2016. (December 2017) - Aye, Goodness C.; Carcel, Hector; Gil-Alana, Luis A.; Gupta, Rangan
Abstract: This paper examines the inflation hedging ability of gold in the UK based on a fractional integration and cointegration framework. This gives more flexibility as it does not restrict the order of integration between zero and 1. Annual time series data covering 1257–2016 were used. We conducted both full sample and sub-sample analysis. Using the full sample, the findings shows that gold and retail price index (RPI) are both I(1). However, based on the sub-sample analyses, gold is I(1) for most sub-periods while RPI is mean reverting (d < 1) for most periods. However, both series exhibit the same degree of integration, I(1), during the last sub-sample, specifically between 1903 and 2016. We also find the existence of cointegration between gold and RPI but this is exclusively due to the data from the last century. It is therefore concluded that gold provides protection against inflation since its value would be maintained in the presence of inflation. Highlights: We investigate inflation hedging ability of gold from 1257 to 2016. Fractional integration and cointegration framework was used. Gold and retail prices are I(I) in the last sub-sample. Gold is found to be a hedge for inflation.